Acclimatization of phalaenopsis and cattleya obtained by micropropagation (2010)
Título en español: Aclimatización de Phalaenopsis y Cattleya obtenidas por micropropagación ABSTRACT The quality of micropropagated plants relies on the acclimatization stage. This research intends to develop an efficient protocol to obtain the acclimatization of Phalaenopsis and Cattleya. Plants of Phalaenopsis obtained from protocorms were selected. They came from flowering stalks grown at modified Murashige and Skoog (MS) (1962) medium and classified by growth ranks and put into moss, mesquite wood shaving and perlite (1:1:1), into a humidity chamber. The protocorms were multiplied at MS from Cattleya sown in Knudson C (1946) medium; regenerated plants of 1-2 cm were selected, and implanted in humidity chamber on: moss, coal and perlite (1:1:1) MCP; mesquite wood shavings, coal and perlite (1:1:1) ACP; moss and perlite (1:1) MP; mesquite wood shaving and perlite (1:1) AP. The following results were obtained: Phalanopsis: a) Survival: 44% in R0 and 100% in RI and RII of the. b) Number of leaves: RI gave on average 1 more leaf than the range 0; c) Roots number and length: RI and RII gave on average 2 more roots than R0, and there were no significant differences in length. d) Height: RII presented greater growth than RI and Ro. Cattleya: a) The survival in MCP was 0%, MP 16 %, ACP 32% and AP 80%. b) The height in MP was significantly superior to the ones in ACP and AP. Plants from both genera need to achieve a 2 to 4 cm growth rank in vitro to endure the greenhouse conditions. MAP was the best substrate in Phalaenopsis and moss-perlite in Cattleya. Key words: Orchidaceae, substrates, in vitro culture. RESUMEN La calidad final de las plantas producidas por micropropagación depende de la etapa de aclimatización. Se intenta desarrollar un protocolo eficiente para la aclimatización de Phalaenopsis y Cattleya. Se seleccionaron plantas de Phalaenopsis, obtenidas de protocormos provenientes de estacas florales cultivadas en Murashige y Skoog modificado (MS) (1962), por rangos de crecimiento e implantadas en musgo, viruta de algarrobo y perlita (1:1:1), en cámara húmeda. De siembras de Cattleya en medio de Knudson C (1951) se multiplicaron protocormos en MS; se seleccionaron plantas regeneradas de 1-2 cm, e implantadas en cámara húmeda en los sustratos: musgo, carbón y perlita (1:1:1) MCP; viruta de algarrobo, carbón y perlita (1:1:1) ACP; musgo y perlita (1:1) MP; viruta de algarrobo y perlita (1:1) AP. Se obtuvieron los siguientes resultados: en Phalaenopsis: a) Supervivencia: para R0 de 44% y RI y RII del 100%; b) número de hojas: RI generó en promedio 1 hoja más que el rango 0; c) número y longitud de raíces: RI y RII generaron en promedio dos raíces más que R0, no detectándose diferencias significativas en longitud; d) altura: RII presentó mayor crecimiento que RI y R0 En Cattleya: a) La supervivencia en MCP fue 0%, MP 16%, ACP 32% y AP 80%; b) La altura en MP resultó significativamente superior que en ACP y AP. Ambos géneros necesitan alcanzar un crecimiento de 2 a 4 cm in vitro para tolerar las condiciones de invernáculo. El mejor sustrato fue MAP en Phalaenopsis, y la mezcla musgo-perlita en Cattleya. Palabras clave: Orchidaceae, sustratos, cultivo in vitro.